Seeing though the clutter: A case report of Posterior Cortical Atrophy and patient-centered care. Issue 1 (2nd January 2022) - Bailey, K. Chase; Sandlin, Emily K.; Brickell, Emily E.; Gardner, Ashley
Abstract: Objective: Posterior cortical atrophy (PCA) is a neurodegenerative disease, with complex and heterogeneous neurological/neuropsychological sequelae but with similar pathophysiology to Alzheimer's disease. This case report demonstrated the complexity of this disorder and the challenges from the provider and patient perspective. Method: Case report focused on a 57-year-old, Caucasian, right-handed woman. Initially, presentation with chronic headaches, vague cognitive complaints, and seemingly confounding mood factors triggered a referral to neurology with a normal neurological exam, grossly normal cognitive performance on a screening measure, and normal imaging studies. Results: After serial neuropsychological evaluation, antidepressant medication therapy, and a successful course of psychotherapy to address past trauma, evolution of symptoms (i.e., Gerstmann's syndrome and visuoperceptual deficits) allowed for a diagnosis of PCA to be reached. Follow-up interview with patient and her partner gave unfiltered insight into the personal impact of living with PCA. Conclusions: With high-quality patient-centered care, the burden of coping with progressively debilitating deficits is slightly lessened. As said best by the patient, "to me it's awful" and balanced by her partner's reminder of "cherishing every good moment."